2015
DOI: 10.1016/j.catena.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphology and evolution of the late Pleistocene to Holocene fluvial system in the south-eastern Llanos de Moxos, Bolivian Amazon

Abstract: In the Bolivian Amazon several paleochannel generations are preserved. Their wide spectrum of morphologies clearly provides crucial information on the type and magnitude of geomorphic and hydrological changes within the drainage network of the Andean foreland. Therefore, in this study we mapped geomorphological characteristics of paleochannels, and applied radiocarbon and optically stimulated luminescence dating. Seven paleochannel generations are identified. Significant changes in sinuosity, channel widths an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 65 publications
(83 reference statements)
2
20
0
Order By: Relevance
“…The results of this study, combined with other published data (Guyot et al, 1996;Lombardo, 2014;do Nascimento Jr. et al, 2015;Plotzki et al, 2015), suggest that these small rivers are highly active and play a dominant role in shaping the SAFB alluvial plains. These rivers, and in particular the Sécure, Isiboro, Moleto, Maniqui, Piraí and Grande rivers, show extremely reduced meander migration rates downstream from where the crevasses opened up (for example Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of this study, combined with other published data (Guyot et al, 1996;Lombardo, 2014;do Nascimento Jr. et al, 2015;Plotzki et al, 2015), suggest that these small rivers are highly active and play a dominant role in shaping the SAFB alluvial plains. These rivers, and in particular the Sécure, Isiboro, Moleto, Maniqui, Piraí and Grande rivers, show extremely reduced meander migration rates downstream from where the crevasses opened up (for example Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Stratigraphic cores performed across the alluvial plain have shown that, since the mid-Holocene, distributary fluvial systems formed by the Mamoré's tributaries (Fig. 1) have deposited thick layers of sediments over the southern and central part of the LM (Lombardo, 2014;Plotzki et al, 2015). This region hosts one of the most important collections of pre-Columbian earthworks in Amazonia, including monumental mounds, raised fields, ring ditches, fish weirs, canals and causeways (Lombardo et al, 2011;Prümers and Jaimes Betancourt, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…A different situation is found on the eastern side of the Mamoré River, the furthest away from the Andes. Most of this area was covered with a sedimentary lobe deposited by the Río Grande (Lombardo et al, 2012;Plotzki et al, 2015). All the samples that indicate a vegetation shift from SF savannah to Forest are located here.…”
Section: Results and Interpretationmentioning
confidence: 96%
“…The southern movement of the South American Summer Monsoon caused an increase in precipitations at about 4 to 3 kyr BP and the southward expansion of the Amazonian rainforest into north-eastern LM at the expense of the savannah (Carson et al, 2014;Mayle et al, 2000). Large scale river shifts, such as those of the Beni River (Dumont, 1996), the Mamoré (Plotzki et al, 2013), the Grande River (Lombardo et al, 2012;Plotzki et al, 2015) and several other tributaries of the Mamoré (Lombardo, 2014;Lombardo, 2016), formed fluvial distributary systems that covered most of the CSM (Lombardo et al, 2018). During the late Holocene, the combined action of strong winds and waves formed the hundreds of geometric and oriented lakes that dot the LM landscape (Lombardo and Veit, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alluvial surface soils in the LM show abundant pedological evidence for dominantly hydromorphic conditions (Boixadera et al, 2003). Recent studies on the type and chronologies of the paleochannel systems in the LM inundation savannah have documented large-scale changes in inundation patterns and/or frequencies, likely as the result of the interplay between environmental and tectonic drivers (Plotzki et al, 2011;Lombardo, 2014;Plotzki et al, 2015). In this context, periods of reduced flooding intensities in the southeastern LM seem to be expressed in the development of regional-scale paleosols, which underlie mid-to late Holocene fluvial and lacustrine sediments (Lombardo et al, 2012), or are exposed in cut-banks along the outer meanderbelts of most major rivers in the LM (Iriondo, 1999).…”
Section: Introductionmentioning
confidence: 99%